P11.08 Defining EGFR amplification status for clinical trial inclusion. (6th September 2019) - French, P; Eoli, M; Sepulveda, J; de Heer, I; Kros, J M; Walenkamp, A; Frenel, J; Franceschi, E; Clement, P; Weller, M; Ansell, P; Looman, J; et al.
Abstract: BACKGROUND: Precision medicine trials targeting the epidermal growth factor receptor (EGFR) in glioblastoma patients require selection for EGFR -amplified tumors. However, there is currently no golden standard in determining the amplification status of EGFR or EGFRvIII expression. Here, we aimed to determine which technique and which cut-offs are suitable to determine EGFR amplification status. MATERIAL AND METHODS: We compared fluorescent in-situ hybridization (FISH) and RT-qPCR data from patients screened for trial inclusion into the Intellance 2 clinical trial, with data from a panel-based next generation sequencing (NGS) platform (both DNA and RNA). RESULTS: By using data from >1000 samples, we show which cut-offs are optimal to determine EGFR gene amplification by FISH. Our data also show that gene amplification (as determined by FISH) correlates with EGFR expression levels (as determined by RT-qPCR) with ROC analysis showing an under the curve area of up to 0.902. EGFR expression as assessed by RT-qPCR therefore may function as a surrogate marker for EGFR amplification. Our NGS data shows that EGFR copy numbers can strongly vary between tumors with levels ranging from 2 to more than 100 copies per cell. Levels exceeding 5 gene copies can be used to define EGFR-amplification by NGS; below this level FISH detects very few (if any) EGFR amplified nuclei and none of the samples express EGFRvIII . CONCLUSION: Our data from central laboratories and diagnostic sequencing facilities, using material from patients eligible for clinical trial inclusion, help defining the optimal cut-off for various techniques to determine EGFR amplification for diagnostic purposes.